Investigation of Atmospheric Pollution by Biomonitoring of Major and Trace Elements in an Industrial Region - Kara, Melik; Odabasi, Mustafa; Dumanoglu, Yetkin; Falay, Ezgi Ozgunerge; Tuygun, Gizem Tuna; Altiok, Hasan; Bayram, Abdurrahman; Tolunay, Doganay; Elbir, Tolga (Journal of Environmental Science and Engineering Technology, 2019)
Spatial variations and sources of atmospheric pollution by measuring of 48 major and trace elements were determined in Iskenderun industrial region using tree components samples (pine needle, bark, branch, stem and litter) and soil samples taken from 21 industrial sites and 6 background sites. The highest elemental concentrations were found at industrial sites and generally a decreasing trend with distance was observed. For most of the crustal elements, contamination factors (CF, element concentration in polluted area/element concentration in background area) were low (< 2). For Bi, Cr, Pb, Sn, and Zn, the Iskenderun region was classified as seriously contaminated (8 < <CF> < 27), while for several elements, including Cd, Ag, Cr, As, Fe, Mn, Sn, Mo, Se, Pb, Ni, Sb and Zn the region was classified as moderately contaminated (3.5 < <CF> < 8). Sources of trace elements in Iskenderun industrial region were investigated using Principal Component Analysis (PCA). PCA have identified four factors as crustal-resuspended particulate matter, iron-steel plant emissions, marine aerosol, and accumulation of nutrient elements on plants. Spatial variations of anthropogenic-based trace elements supported the finding that iron-steel facilities are their major sources in the Iskenderun industrial region. Results of this study confirmed that tree components and litter can be used as passive samplers to explore the geographical distribution of atmospheric pollution.